Alloimmunization in Congenital Deficiencies of Platelet Surface Glycoproteins: Focus on Glanzmann's Thrombasthenia and Bernard–Soulier's Syndrome - Poon, Man-Chiu; d'Oiron, Roseline (Seminars in Thrombosis and Hemostasis, 2018)
Glanzmann's thrombasthenia (GT) and Bernard–Soulier's syndrome (BSS) are well-understood congenital bleeding disorders, showing defect/deficiency of platelet glycoprotein (GP) IIb/IIIa (integrin αIIbβ3) and GPIb-IX-V complexes respectively, with relevant clinical, laboratory, biochemical, and genetic features. Following platelet transfusion, affected patients may develop antiplatelet antibodies (to human leukocyte antigen [HLA], and/or αIIbβ3 in GT or GPIb-IX in BSS), which may render future platelet transfusion ineffective. Anti-αIIbβ3 and anti-GPIb-IX may also cross the placenta during pregnancy to cause thrombocytopenia and bleeding in the fetus/neonate. This review will focus particularly on the better studied GT to illustrate the natural history and complications of platelet alloimmunization. BSS will be more briefly discussed. Platelet transfusion, if unavoidable, should be given judiciously with good indications. Patients following platelet transfusion, and women during and after pregnancy, should be monitored for the development of platelet antibodies. There is now a collection of data suggesting the safety and effectiveness of recombinant activated factor VII in the management of affected patients with platelet antibodies.
Keywords: Glanzmann's thrombasthenia; Bernard–Soulier's syndrome; platelet transfusion; alloimmunization; platelet antibodies; HLA antibodies; αIIbβ3 (GPIIb/IIIa) antibodies; GPIb-IX antibodies; rFVIIa; pregnancy